Relaxing Intertemporal Separability: A Rational Habits Model of Labor Supply Estimated from Panel Data - Bover, Olympia (Journal of Labor Economics, 1991)
This article relaxes the assumption of separability of preferences over time that, although implausible, is usually maintained in life-cycle labor-supply models. An empirically tractable rational habits model is specified and estimated on the basis of a 10-year sample of men from the Michigan Panel of Income Dynamics. The effect of past hours of work in determining current hours decisions is found to be very important and well determined, having allowed for permanent individual differences and for time effects.